On the Critical Size of the Transition of a Ferromagnet into a Single-Domain State - Yu.O. Tykhonenko-Polishchuk; A.I. Tovstolytkin (Журнал нано- та електронної фізики)
The analysis of approaches for determining the critical size of the transition of a ferromagnet into a single-domain state (dcr) was performed, and generalizations for the cases of magnetic materials with different types of anisotropy and for particles of elliptical shape were made. The criteria for the applicability of each of the analyzed approaches have been clarified. Typical errors that occur in the scientific literature for estimating dcr were identified. The dcr values for the most common ferromagnetic materials have been calculated, and the obtained results have been compared with the available experimental data. Data on the magnetic parameters of the most common ferromagnetic materials have been ordered and systematized.